Enhancement of the ballistic performance of aramid fabric with polyurethane and shear thickening fluid. (November 2020) - Wang, Xingwei; Zhang, Jianbin; Bao, Luyao; Yang, Wufang; Zhou, Feng; Liu, Weimin
Abstract: Conventionally, the shear thickening fluid (STF) is used to improve the ballistic performance of aramid fabric because its shear thickening property increases the friction of inter-yarns. However, intuitively, enhancing the inter-yarn adhesion is an easier method. In this study, the adhesive polyurethane (PU) was utilized. The aramid fabrics impregnated with STF, the composite of STF and PU (STF-PU), and PU were compared in terms of the resistance to single yarn pull-out, the flexibility of fabric and the high-velocity impact test, respectively. Due to the robust adhesion of PU, comparing with STF/aramid fabric, a small amount of PU within STF-PU could strengthen the resistance of inter-yarn relative motion significantly and decrease mass loading intensively. Meantime, the flexibility had a little compromise due to unique heterogeneous structure in striking contrast with PU/aramid whose flexibility was impaired extremely. When it came to the high-velocity impact test, STF-PU/aramid showed outright advantages over STF/aramid and PU/aramid composite. It was also illuminated that excessively strong resistance to the yarn mobility was adverse for the high-velocity impact. Confidently, this work provides a new avenue in the development of flexible armor. Graphical abstract: Unlabelled Image Highlights: Polyurethane (PU) was innovatively used to improve the ballistic performance of shear thickening fluid (STF)/Aramid fabric. Comparing with conventional STF/Aramid fabric, the ballistic performance was enhanced tremendously. The mass loading decreased greatly against the same ballistic performance.